Preventing malfeasance in low corruption environments: twenty public administration responses. Issue 1 (2nd January 2018) - Graycar, Adam; Masters, Adam B.
Abstract : Purpose: Corruption undermines good governance. Strategies for preventing malfeasance in low-corruption environments require a different approach to that applied in high-corruption environments. This paper aims to ask if criminological theories and practice contribute to the study and prevention of corruption in public organizations? Do crime prevention techniques help us in preventing corruption? Design/methodology/approach: Empirical data demonstrate that the overwhelming majority of public officials in rich countries demonstrate high levels of integrity; yet, significant sums are invested in anti-corruption agencies and prevention strategies. This paper reports on recent work with an anti-corruption agency, which forced us to re-think how to deliver an anti-corruption agenda in a low-corruption environment. The authors build on their research of public sector corruption in rich countries to develop a set of 20 situational corruption prevention measures for public administrators. Findings: The result, with lessons from crime prevention, is a prevention tool to support continued good governance in low-corruption environments. Figure 1 is a template that readers can apply in their own environments. Figure 2 is the authors' attempt to populate this template based on the research reported here. Originality/value: The matrix of situational corruption prevention techniques provides two original approaches. First, it recasts the language of crime prevention into a non-confrontational approach to avoid alienating honest public officials. Second, the matrix incorporates common public sector functions to guide the development of context specific corruption prevention techniques.